Core body temperatures in intermittent sports: a systematic review - Henderson, M. J.; Grandou, C.; Chrismas, B. C. R. (Sports Medicine, 2023)
Background: Hyperthermia (and associated health and performance implications) can be a significant problem for athletes and teams involved in intermittent sports. Quantifying the highest thermal strain (i.e. peak core body temperature [peak Tc]) from a range of intermittent sports would enhance our understanding of the thermal requirements of sport and assist in making informed decisions about training or match-day interventions to reduce thermally induced harm and/or performance decline. Objective: The objective of this systematic review was to synthesise and characterise the available thermal strain data collected in competition from intermittent sport athletes. Methods: A systematic literature search was performed on Web of Science, MEDLINE, and SPORTDiscus to identify studies up to 17 April 2023. Electronic databases were searched using a text mining method to provide a partially automated and systematic search strategy retrieving terms related to core body temperature measurement and intermittent sport. Records were eligible if they included core body temperature measurement during competition, without experimental intervention that may influence thermal strain (e.g. cooling), in healthy, adult, intermittent sport athletes at any level. Due to the lack of an available tool that specifically includes potential sources of bias for physiological responses in descriptive studies, a methodological evaluation checklist was developed and used to document important methodological considerations. Data were not meta-analysed given the methodological heterogeneity between studies and therefore were presented descriptively in tabular and graphical format. Results: A total of 34 studies were selected for review; 27 were observational, 5 were experimental (2 parallel group and 3 repeated measures randomised controlled trials), and 2 were quasi-experimental (1 parallel group and 1 repeated measures non-randomised controlled trial). Across all included studies, 386 participants (plus participant numbers not reported in two studies) were recruited after accounting for shared data between studies. A total of 4 studies (~ 12%) found no evidence of hyperthermia, 24 (~ 71%) found evidence of `modest` hyperthermia (peak Tc between 38.5 and 39.5 °C), and 6 (~ 18%) found evidence of `marked` hyperthermia (peak Tc of 39.5 °C or greater) during intermittent sports competition. Conclusions: Practitioners and coaches supporting intermittent sport athletes are justified to seek interventions aimed at mitigating the high heat strain observed in competition. More research is required to determine the most effective interventions for this population that are practically viable in intermittent sports settings (often constrained by many competing demands). Greater statistical power and homogeneity among studies are required to quantify the independent effects of wet bulb globe temperature, competition duration, sport and level of competition on peak Tc, all of which are likely to be key modulators of the thermal strain experienced by competing athletes.